Towards Interoperability in Clinical Research - Enabling FHIR on the Open-Source Research Platform XNAT. - Khvastova, Maryna; Witt, Michael; Essenwanger, Andrea; Sass, Julian; Thun, Sylvia; Krefting, Dagmar (Journal of Medical Systems, 2020)
This paper presents an approach to enable interoperability of the research data management system XNAT by the implementation of the HL7 standards framework Fast Healthcare Interoperability Resources (FHIR). The FHIR implementation is realized as an XNAT plugin (Source code: https://github.com/somnonetz/xnat-fhir-plugin), that allows easy adoption in arbitrary XNAT instances. The approach is demonstrated on patient data exchange between a FHIR reference implementation and XNAT.